(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
The Greeks introduced the "mathematical" under the determination of: things, as they arise and present themselves; things as they are produced by hand by man, and are present as such; Things, insofar as they are in use and in permanent disposition, can be stones and similar things, or expressly manufactured things with which we deal, whether we define them, use them or transform them, or whether we only contemplate them (Heidegger, 1975). Regarding deep disagreements, Robert J. Fogelin asks in his work: What happens to arguments when the context is neither normal nor close to normal? and under this panorama he dares to say that the argumentative context becomes less normal, and argumentation to this extent becomes impossible, and he tries to leave – initially – for said event by the way, that the conditions for argumentation do not exist, and that The language of argument may persist, but it ends up being useless since it appeals to something that does not exist: a shared background of beliefs and preferences. Under a qualitative analysis, and situated in the classroom, the heuristic route is projected to provide a solution to a problem that nests in geometry.